European social model in making : European Commission reporting on Romania between 1999-2006 - Heikkilä, Konsta (2007)
The European Union is often described as being an economic giant but a political dwarf. True enough, the European project started with economics, but has gone a long way since the time that it was only about economy. In Europe, there are obviously many different types of social models and welfare regimes. In addition to national models and regimes, there is an ongoing process at the European level that can be characterised as a search for “European social model”. This process involves both the institutions of the European Union as well as the member states. Political (and economic) battle that is being waged concentrates on what “European social model” should look like and who gets to define it. For its part, the European Commission is fond of the term “European social model”, which implies societies supposedly being based on a certain set of shared values and a willingness to act upon these values. Member states, on the other hand, often highlight the differences instead of similarities in social models and welfare regimes found across Europe. One of the success stories of European integration is the successive waves of enlargement, a process in which the EU can be seen to be using its economic and political power. With the previous EU enlargements, social rights or social condition did not play a key role for two reasons: firstly, integration meant mainly economic integration and, secondly, there was no deficit in social rights and the social condition in acceding states was equal or in fact surpassed the condition in the existing member states. However, all this changed after the fall of communism and the new situation in Eastern and Central Eastern Europe. This study focuses on Commission Regular reports on Romania between 1999 and 2006. The primary sources are the Regular reports on Romania’s progress towards membership prepared by the Commission. Some of the questions that arise in the study are: How are social rights and social policy dealt with in Regular reports? Concerning social rights and social policy, which issues does the Commission bring up and concentrate on in its reporting on Romania? And, finally, what does the European social model look like when it is constructed from the analysis of Commission Regular reports on Romania between 1999 and 2006? It is suggested that in the area of social rights and social policy the competence of the Commission, and the way in which Commission uses conditionality, can be described as being functional rather than legal in nature. Furthermore, it is argued that the Commission could take a tougher stand regarding social rights and social policy without a risk of losing its credibility and influence towards the acceding states. Based on this study it seems clear that the Commission advocates a social model based on active employment and labour market policies. To describe the European Union as being an economic giant but a political dwarf is maybe outdated, this study suggests that the EU should be called an economic giant, political half-ling and a social dwarf.